The Canadian money market experiment - WILSON, J.S.G. (PSL Quarterly Review, 2014)
The article describes the effort by the Canadian Central Bank to support and actively sponsor the establishment of a short-term money market. Such markets facilitate to a great degree monetary policy through the control of the activities of commercial banks. The first steps by the Central Bank were taken in March of 1934 and the experiment took on several stages until 1957. JEL: E52, E58, E65